2015
DOI: 10.1111/1750-3841.13173
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Virulence Genes and Growth Potential in Listeria monocytogenes Strains Isolated from Ricotta Salata Cheese

Abstract: Ricotta Salata is a traditional ripened and salted whey cheese made in Sardinia (Italy) from sheep's milk. This product is catalogued as ready-to-eat food (RTE) since it is not submitted to any further treatment before consumption. Thus, foodborne pathogens, such as Listeria monocytogenes, can represent a health risk for consumers. In September 2012, the FDA ordered the recall of several batches of Ricotta Salata imported from Italy linked to 22 cases of Listeriosis in the United States. This study was aimed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
13
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 37 publications
5
13
1
Order By: Relevance
“…In this study, plcA and iap which code for phospholipase and invasion-associated protein respectively, occurred in 100% of the isolates. This is also higher than the prevalence noticed in other studies [53,[55][56][57]. The variations in the prevalence of virulence markers detected in this study and that observed in other studies may be due to the differences in the origin or source of the isolates.…”
Section: Discussioncontrasting
confidence: 69%
“…In this study, plcA and iap which code for phospholipase and invasion-associated protein respectively, occurred in 100% of the isolates. This is also higher than the prevalence noticed in other studies [53,[55][56][57]. The variations in the prevalence of virulence markers detected in this study and that observed in other studies may be due to the differences in the origin or source of the isolates.…”
Section: Discussioncontrasting
confidence: 69%
“…In previous studies, Khedr et al [39] detected inlA and inlB genes in 100% and 75% of examined L. monocytogenes isolates, respectively. However, Coroneo et al [57] recorded inlA and inlB genes in 60% and 47% of L. monocytogenes strains recovered from Ricotta salata cheese, respectively.…”
mentioning
confidence: 98%
“…The differences in the distribution of virulence internalin genes could be attributed to the source of samples or L. monocytogenes serotype or mutations in these genes resulted in reduction in invasion or virulence in animal model studies or tissue culture, assuring the significant role of such genes in the pathogenesis and virulence of L. monocytogenes [57][58][59]. It was noticed that 12 isolates of L. monocytogenes carry inlA gene and 6 isolates carry inlB gene that indicates virulent strains of L. monocytogenes and creates hazard in dairy farms as well as milk handlers, milk consumers and pregnant women.…”
mentioning
confidence: 99%
“…Several recent studies have focused on the growth potential of L. monocytogenes in different RTE food products (Awaiwanont, Smulders, & Paulsen, 2015;Coroneo et al, 2016;Dalzini et al, 2014;Grassi, Nucera, Lomonaco, & Civera, 2013;Jesus et al, 2016;Lahou & Uyttendaele, 2017;Michellon et al, 2016;Sahu, Kim, Ferguson, Zink, & Datta, 2017;Sant'Ana, Barbosa, Destro, Landgraf, & Franco, 2012;Skalina & Nikolajeva, 2010;Spanu et al, 2012;Uyttendaele et al, 2009). These studies intended the classification of foods in the appropriate food category specified in Reg.…”
Section: Resultsmentioning
confidence: 99%